Adapting Contextualized ELT Materials in Sorong Regency: Teachers’ Perspectives and Pedagogical Implications - Nurteteng Nurteteng; Agus Setiawan; Tri Devi Dian Lestari (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2025)
Material adaptation is a pivotal aspect of English Language Teaching (ELT), particularly in culturally and linguistically diverse settings. This study examines the perceptions of junior high school teachers in Sorong Regency, Southwest Papua, regarding contextualized ELT material adaptation, with a focus on challenges encountered and perceived impacts on student engagement and learning. Employing a qualitative descriptive design, data were collected from five experienced ELT teachers through semi-structured interviews. The findings indicate that teachers actively contextualize materials by integrating local culture, environmental themes, and student experiences to enhance relevance and motivation. Despite notable challenges such as varied proficiency levels, limited resources, and technological gaps, teachers observed improvements in comprehension, participation, and academic performance. The study underscores the importance of culturally responsive pedagogy and calls for targeted professional development and resource allocation to support ELT in underrepresented regions.